Research on the construction of a service quality evaluation system for university student dormitories based on the Delphi method - Zhang, Caining; Zhao, Chunyu (Frontiers in Education, 2024)
Student dormitories play a pivotal role in the daily lives of university students in China, significantly impacting their academic, residential, and developmental experiences. This research aims to develop a customized service quality evaluation index system tailored for Chinese university dormitories. Utilizing the Delphi method and the Analytic Hierarchy Process (AHP), fifteen experts from Chinese universities deliberated on 28 initial indicators over two rounds, resulting in six primary and 23 secondary indicators. This framework aligns with the specific requirements of Chinese university dormitories and sets a robust technical foundation for future evaluations, enhancing dormitory management practices across China.